A novel 12‐hour versus 24‐hour magnesium sulfate regimen in the management of eclampsia and preeclampsia in Ghana (MOPEP Study): A randomized controlled trial. Issue 2 (6th April 2022) - Beyuo, Titus K.; Lawrence, Emma R.; Kobernik, Emily K.; Oppong, Samuel A.
Abstract: Objective: We compared the efficacy of a 12‐h versus 24‐h regimen of intramuscular magnesium sulfate in the management of eclampsia and preeclampsia. Methods: This is an open‐labeled parallel randomized controlled trial conducted in Accra, Ghana from November 2018 to November 2020. Participants were adult pregnant women admitted to the Korle Bu Teaching Hospital (KBTH) with a diagnosis of antepartum, intrapartum, or postpartum eclampsia or preeclampsia with severe features, having received no more than a loading dose of magnesium sulfate prior to admission at KBTH. Participants in the standard 24‐h group received a loading dose of magnesium sulfate 4 g intravenous and 10 g intramuscular (5 g in each buttock) followed by six, 5 g intramuscular maintenance doses over 24 h. Participants in the 12‐h intervention group received the same loading dose followed by three, 5 g intramuscular maintenance doses over 12 h. The primary outcome was occurrence of seizure after completion of the assigned magnesium sulfate regimen. Secondary outcomes were magnesium sulfate toxicity, magnesium sulfate side effects, maternal outcomes (mode of delivery, duration of inpatient admission, duration of urethral catheterization), maternal complications (pulmonary edema, acute kidney injury, intensive care unit admission, death), and neonatal outcomes. Results: Among 1176 total participants, we found no difference in occurrence of seizure after completion of the assigned regimen in the 24‐h group ( n =  5, 0.9%) versus the 12‐h group ( n =  2, 0.3%), P =  0.29; RR 0.40, 95% CI 0.08, 2.04), or in occurrence of seizure any time after enrollment ( n =  9, 1.5% vs. n =  5, 0.9%, P =  0.28, RR 0.55, 95% CI 0.19–1.64). Participants in the 12‐h group had a shorter duration of inpatient admission (9.4 ± 8.8 vs. 7.7 ± 6.5 days, P =  0.0009) and urethral catheterization (2.1 ± 1.0 vs. 1.9 ± 1.3 days, P <  0.0001). Rates of side effects from magnesium sulfate were lower in the 12‐h group: pain at the injection site (94.8% ( n =  548) vs. 91.5% ( n =  540), P =  0.03), inflammation (62.2% ( n =  358) vs. 40.0% ( n =  237), P <  0.0001), and bleeding or bruising at the injection site (25.1% ( n =  144) vs. 14.4% ( n =  85), P <  0.0001). Conclusions: Compared with 24 h, 12 h of intramuscular magnesium sulfate showed similar rates of seizures, with fewer side effects and shorter inpatient admission. Trial Registration: Prospective registration was with Pan African Clinical Trial Registry (PACTR201811515303983): https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=4690 .